STUDY OF THE INFLUENCE OF COAL CHARACTERISTICS OF THE MEULABOH BASIN AND SOUTH SUMATRA ON GASIFICATION REACTIVITY USING THERMOGRAVIMETRIC ANALYSIS - Bagas Suseno, Ozan
Coal resources in Indonesia are quite abundant and have the potential to be further developed through the gasification process for more environmentally friendly utilization. Gasification reactivity is one of the essential parameters in designing and operating gasification reactors. The characteristics of coal in Indonesia need to be studied in order to know its effect on gasification reactivity. Two samples were from Musi Rawas, South Sumatra (SM01) and West Aceh, Aceh (SM02). The method of testing gasification reactivity uses thermogravimetric analysis, which focuses on the thermal characteristics of the pyrolysis and gasification processes. Thermogravimetric analysis carried out includes heating the sample from 50°C to 900°C with a temperature increase of 10°C/min using an Argon (Ar) atmosphere, conditioning the sample for 10 minutes at 900°C to obtain an isothermal state, and changing the atmosphere to 25% air and 75% Argon (Ar). Coal characteristics were interpreted from the proximate analysis and calorific value test results. SM01 coal is rated sub-bituminous A, and SM02 coal is rated sub-bituminous C. The TG/DTG curves show that both samples undergo five stages in the pyrolysis process: the dehydration stage, slow pyrolysis stage, fast pyrolysis stage, fast polycondensation stage, and slow polycondensation stage. In the gasification process with limited O2, sample SM02 showed more mass reduction, so its reactivity was higher than sample SM01. Lower rank coals are more reactive in the coal gasification process because they are more porous in structure, have a larger active surface area, and have functional groups with more oxygen content. Gasification reactivity can also increase due to the presence of compounds or minerals that provide a catalytic effect on the gasification reaction.